2010
DOI: 10.1159/000296286
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Hypercholesterolemic Diet on Erectile Responses in Rats

Abstract: Objective: The aim of this study was to evaluate the acute effects of a high cholesterol diet (HCD) on erectile and endothelial functions in Sprague-Dawley rats. Materials and Methods: Sprague-Dawley rats were divided into 2 groups as control and HCD groups. The control group was fed on a normal diet and the hypercholesterolemia group was fed a 1% cholesterol-enriched diet daily for 2 weeks. Total cholesterol levels were measured at the end of 2 weeks in both groups. To examine the effect of HCD on erectile fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Whereas they revealed diabetes as only factor associated with penile atherosclerosis. In addition some experimental studies exhibited that erectile function were significantly damaged in hyperlipidemic conditions because of some structural change of penile vessels [30, 31]. Our study did not show any relation between impaired lipid profile or hypertension, the known risk factors of atherosclerosis, and ED in patients with T2DM.…”
Section: Discussioncontrasting
confidence: 44%
“…Whereas they revealed diabetes as only factor associated with penile atherosclerosis. In addition some experimental studies exhibited that erectile function were significantly damaged in hyperlipidemic conditions because of some structural change of penile vessels [30, 31]. Our study did not show any relation between impaired lipid profile or hypertension, the known risk factors of atherosclerosis, and ED in patients with T2DM.…”
Section: Discussioncontrasting
confidence: 44%
“…Several studies in animal models of vasculogenic ED reported endothelial dysfunction in the penile vascular bed occurring prior to this effect in the aorta, coronary, and mesenteric arteries, supporting our findings. For example, in rats fed high cholesterol or Western diet, erectile function was impaired after 2 and 8 weeks, respectively, while endothelium-dependent relaxation of the thoracic aorta and coronary artery were maintained at these times (Demir et al, 2010; La Favor et al, 2013). In obese Zucker rats, a genetic model of insulin resistance, endothelium-dependent relaxation in the dorsal penile artery was decreased at the time (17–18 week of age) when no endothelial dysfunction was present in the coronary artery (Villalba et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Erectile function was measured by electrical stimulation of the cavernous nerve which was performed with pulse duration of 1 ms for 1 min at 5 V and 20 Hz. ICP and MAP were measured as described previously (Bal et al., ; Demir et al., ; Figure ).…”
Section: Methodsmentioning
confidence: 99%